Asset-backed securities: The key to unlocking Europe's credit markets? - Carlo Altomonte; Patrizia Bussoli (Bruegel, 2014)
Direct European Central Bank intervention in the market for asset-backed securities (ABS) has the potential to become, under certain conditions, a mechanism to unlock credit markets in the euro area. When and how the ECB acts will be significant. Acting immediately to purchase existing eligible ABS products (simple structures with corporate credit exposure) is likely to produce little direct effect, given the small size of the available market, estimated at some exteuro68 billion. However, beneficial indirect effects could arise, because of the freeing up of capital on banks' balance sheets, thus creating greater opportunities for banks to access the ECB's targeted longer-term refinancing operation (TLTRO) programme, because more loans can be granted with the same amount of capital. Improving the regulatory environment for ABS products could help revitalise a market that can be conservatively estimated at exteuro3 trillion for the euro area when all types of ABS are included, but regulatory change requires time. Finally, the ECB could purchase existing residential mortgage-backed securities. This would be an immediate and sizeable intervention (up to exteuro500 billion, which could become exteuro1.6 trillion if the ABS market is revitalised), but this option would have elements that overlap with fiscal policy, and should be considered with care.
Keywords: 330